Analysis of some dual properties in discrete dynamic systems - Zhirabok, Alexey (Zielona Góra: Uniwersytet Zielonogórski)
The problem of duality in nonlinear and linear systems is considered. In addition to the known duality between controllability and observability, new dual notions and their properties are investigated. A way to refine these properties through an isomorphic transformation of the original systems is suggested.
Keywords: nonlinear and linear systems; algebraic approach; error correction; reachability; duality